Agroturismo y Oferta turística en el cantón Penipe, Provincia de Chimborazo. - Romero Betancourt, Katiuska Jasmina (2023)
Agrotourism in Ecuador and Latin America is found within the new wave of tourism. There are few studies related to this topic. Therefore, to develop correct research, apply field investigation, documentary, and exploratory. In addition the design it's found integrated to: transversal, correlational, mixed, non-experimental and descriptive for your part to carry out the process analytic it was used the variable touristic offer in the cantón Penipe, province of Chimborazo, due to the nonexistence of data started for lifting two surveys, one for each variable in study, the first applied to the representatives of the seven parochial GADS of the canton because they have data and knowledge from what is dedicated the community, for his part in the tourist offer a base was taken of data collected in work titled "SERVICES AND TOURIST OFFER IN PENIPE CANTON, CHIMBORAZO PROVINCE" carried out by Carlos Donoso Moncayo in which is determined the quantity of establishments that offer services tourist in the canton, with the result of this surveys the respective analysis was carried out having as result preliminary the little knowledge that the community has regard to agrotourism and the confusión what they have between agrotourism and tourism, it's worth say that the surveys first they were subjected to the test Cronbach's Alpha for subsequently carry out the análisis of relation of these two variables, through of the program SPSS was performed the study statistical through Chi squared and raise a game of hypotheses that allowed to determine than agritourism if it significantly influences in the tourist offer of the cantón Penipe, province of Chimborazo, taking into consideration this result to finish this research the autor realize the proposal of a producto tourist denominate "The Route of the Parameter" with the objective of contribute to the community a tourism alternative.